2022
DOI: 10.3389/bjbs.2022.10067
|View full text |Cite
|
Sign up to set email alerts
|

Micro RNA-640 Targeting SLIT1 Enhances Glioma Radiosensitivity by Restraining the Activation of Wnt/β-Catenin Signaling Pathway

Abstract: Purpose: The purpose of this study was to analyze the effects of miR-640–SLIT1 axis and the Wnt/β-catenin signaling pathway on radiosensitivity of glioma cells.Methods: Relative expressions of miR-640 and slit guidance ligand 1 (SLIT1) in glioma tissues and glioma cell lines U251 and A172 were detected using RT-qPCR. The cell lines were transfected with si-SLIT1 or miR-640 inhibitor to study the radiosensitivity of glioma cells. We detected cell activity using CCK-8 assay, cell migration using wound healing as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…MiRNAs play a pivotal role in radiotherapy, modulating tumor radiosensitivity by taking part in DNA repair, cell cycle analysis, apoptosis, autophagy, and ferroptosis [ 7 ]. As an example, Zheng and coworkers revealed that miR-640 potentiated glioma radiosensitivity by focusing on SLIT1 to repress the Wnt/β-catenin flagging pathway [ 8 ]. Recent work by McGrath and colleagues found that manipulating miR-31 expression altered the radiosensitivity of pancreatic ductal adenocarcinoma cells by controlling oxidative pressure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs play a pivotal role in radiotherapy, modulating tumor radiosensitivity by taking part in DNA repair, cell cycle analysis, apoptosis, autophagy, and ferroptosis [ 7 ]. As an example, Zheng and coworkers revealed that miR-640 potentiated glioma radiosensitivity by focusing on SLIT1 to repress the Wnt/β-catenin flagging pathway [ 8 ]. Recent work by McGrath and colleagues found that manipulating miR-31 expression altered the radiosensitivity of pancreatic ductal adenocarcinoma cells by controlling oxidative pressure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%